Clinical improvement and no further need of transplant after closure of PDA with transcatheter approach in an end-stage heart failure patient with hypertrabeculation - Serhat Koca; Feyza Ayşenur Paç; Ajda Mutlu Mıhçıoğlu; Vedat Kavurt; Denizhan Bağrul (KARE Publishing, 2017)
Although heart failure is managed medically most of the time, heart transplantation is still last resort for selected end-stage heart failure patients with noncompaction cardiomyopathy. Presently described for the first time is case of pediatric patient with noncompaction cardiomyopathy who was initially referred to our hospital for heart transplant but underwent PDA repair and improved clinically without need for heart transplant.